SENI KREATIF DI MASA PANDEMI DALAM ALUNAN MUSIK GAMUT (GAMELAN MULUT) - Komang Indra Wirawan (Jurnal Ilmiah Cakrawarti, 2021)
During the Covid-19 pandemic, it did not reduce the enthusiasm of Balinese artists to be productive in their work. Especially with the development of an increasingly advanced era and faster technology, artists can easily hone their creativity through virtual, considering that during this pandemic, the number of people who can gather together is limited. Artists continue to make various efforts to continue to work, one of which is through the YouTube channel which is currently widely used as a place or place for creativity. One of the creative arts that is currently attracting the attention of Balinese people is gamut art or better known as oral gamelan, popularized by artist Made Agus Wardana on his YouTube channel. Artist Made Agus Wardana invites the public to continue to strengthen the fighting spirit of the artists with various efforts, this is done to overcome various obstacles in today's difficult times while maintaining the embers of art.